2008
DOI: 10.1017/s0022149x0804827x
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis associated with chronic cough in childhood: a longitudinal study in Hungary

Abstract: Chronic cough lasting 8 weeks or more often seems to be an intractable problem in childhood. Toxocara infection is associated with an increased prevalence of airway symptoms and may be the possible aetiological agent of chronic cough. Of 425 children aged 2-17 years with chronic cough who were investigated for toxocariasis and the distribution of bronchial asthma (BA), cough variant asthma (CVA) and non-asthmatic eosinophilic bronchitis (NAEB), 136 (32%) were seropositive for Toxocara canis antigens. Ninety-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Infected children may present with a persistent cough which can be treated with anthelminthics (88). However, most pathology associated with VLM occurs in the liver.…”
Section: Visceral Larva Migransmentioning
confidence: 99%
“…Infected children may present with a persistent cough which can be treated with anthelminthics (88). However, most pathology associated with VLM occurs in the liver.…”
Section: Visceral Larva Migransmentioning
confidence: 99%
“…In contrast with the helminth burden in endemic areas, the occurrence of toxocariasis in Hungary is mild and/or sporadic . The majority of our patients with chronic cough came from rural areas.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of toxocariasis in children living in urban areas is estimated to be 10·2% , whereas in developing countries, the seroprevalence is 86% among children living in poor circumstances . An earlier estimate of the seroprevalence for Toxocara in healthy Hungarian children was 17%, as compared with 32% in children with chronic cough .…”
Section: Introductionmentioning
confidence: 91%
“…However, other studies failed to demonstrate an association between Toxocara seropositivity and asthma; one study suggested that this association may be attributed to cross-reactivity. There was also some evidence that treatment of chronic cough with both asthma therapy and anthelminthic may be beneficial (Bede et al, 2008).…”
Section: Introductionmentioning
confidence: 99%